Experimental Investigation into the Production Behavior of Methane Hydrate under Methanol Injection in Quartz Sand - Li, Gang; Wu, Danmei; Li, Xiaosen; Zhang, Yu; Lv, Qiunan; Wang, Yi (Energy & Fuels, 2017)
In this work, the dissociation behavior of methane hydrate in quartz sand sediment by injecting a thermodynamic inhibitor, methanol (MeOH), was investigated using a one-dimensional experimental apparatus. The experimental results indicated that the hydrate dissociation process included four stages: free gas production, methanol dilution, major hydrate dissociation, and residual gas production. The overall liquid production rate was smaller than the injection rate during the whole production process. The cumulative gas produced from hydrate under methanol solution injection was adjusted with the reference experiment. A new strategy of the adjustment of the experimental runs was introduced, which was based on the ratio of the water and methanol solution injection rates. In general, with the increase of the methanol injection rate and the methanol concentration, the cumulative hydrate-originating gas produced increased. During the major hydrate dissociation stage, the production efficiency was enhanced continuously with the increase of the injection rate and concentration of the methanol solution, while the methanol efficiency increased and reached a maximum value when the concentration was 60 wt % and then gradually decreased.